Cooperative Learning Modeldalam Meningkatkan Motivasisiswa Pada Pelajaran Pendidikan Jasmani Olahraga Dan Kesehatan - Suhariyanti, Mela (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of this study was to determine the effect of applying the Cooperative Learning Model to volleyball game material in increasing student motivation. Quantitative research with an experimental approach. The sample in this study amounted to 30 students. The results showed: the sig value for the control class data was 0.082 with a normal distribution and the sig value for the experimental class data was 0.131 (sig. > 0.05) with a normal distribution. Based on the Levene's Test the sig value was 0.196 and the t test with a sig value of 0.000 (sig. <0.05) which indicated that there was a significant difference in the control and experimental classes in increasing student learning motivation where the increase occurred in the experimental class.